TANGGUNG GUGAT PERDATA PENYEDIA PLATFORM ATAS KERUGIAN AKIBAT MALAFUNGSI SISTEM ARTIFICIAL INTELLIGENCE - Dedeh Asmariah; Nadia Mega Yuliah; Agus Septima Ridwan; Syafi'il Anam (JOURNAL OF LAW AND NATION, 2026)
The adoption of artificial intelligence technology in digital banking credit assessment systems raises legal questions that remain inadequately resolved within Indonesian civil law, particularly regarding liability when the system fails and harms customers. This study aims to examine the juridical qualification of artificial intelligence system failures as unlawful acts under Article 1365 of the Indonesian Civil Code, and to formulate the civil liability of platform providers under Article 1367 of the Civil Code. The research employs a normative legal method with statutory and conceptual approaches. The findings indicate that artificial intelligence system failures satisfy all elements of an unlawful act, with fault attributed to the platform provider as the operator of the system rather than to the system itself, which holds the status of an object. Based on the doctrine of vicarious liability and the theory of strict liability, digital banking platform providers bear full responsibility for customer losses and cannot shield themselves behind exoneration clauses in the terms and conditions of service.